Improving Table Tennis Service Skills Through Cooperative Learning: An Experimental Study in Senior High School - Sony Hasmarita; Heru Sulistiadinata; Muchamad Ishak (STKIP Pasundan, 2026)
This study analyzes the effectiveness of cooperative learning in optimizing basic table tennis service techniques for class X students at MA MISBAHUNNUR, Cimahi City. Using a quasi-experimental pretest-posttest control group design, 80 students aged 15–16 years participated (40 experimental, 40 control). The experimental group received STAD-type cooperative learning for 16 sessions, while the control group used conventional methods. A forehand and backhand service skill test (reliability 0.89) served as the instrument. Independent sample t-test analysis revealed significant differences (p < 0.05) between the experimental group (M = 78.45, SD = 6.32) and control group (M = 68.20, SD = 7.15), with effect size d = 1.52 (large). The experimental group showed 34.2% improvement versus 18.6% in the control group. The cooperative learning model effectively optimized table tennis service techniques and positively impacted students' cognitive, affective, and psychomotor development.